Stylistic Peculiarities of the Text of the Academic Lecture (Based on the Material of the English Language) (Proceedings of Southern Federal University. Philology, 2020)
The article analyses some peculiarities in the style of a lecture in modern English. It has been found out that the most important stylistic characteristics include logical sequence, rigor of presentation, clarity, objectivity, monological nature of presentation, semantic capacity and some others. The contents of the lecture is oriented to the scientific community. In spite of the fact that the most part of the lecture is a monologue, the lecture genre has a dialogical character. The text of a lecture often contains citations which illustrate the points of view of different scientists. Functional and stylistic peculiarities of an academic substyle are reflected in the genre of a lecture, in particular, in the lexical, syntactic and grammar characteristics. The style of a lecturer can vary depending on the level of spokenness, which is expressed in the use of rhetorical questions and discourse markers.The author comes to the conclusion that a lecture is a peculiar genre which is created in the written form but which is presented to the audience in the oral or online form. A lecture genre is one of the basic university genres with a long history. There exist different styles of an academic lecture which are subject to changes depending on the academic discipline, personality of a lecturer, as well as modern communication technologies used by the lecturer.A lecture style is a complex notion which incorporates verbal, nonverbal and paraverbal components.Keywords: academic lecture, lecture style, classification of lectures, traditional lecture model, verbal component, extraverbal component.DOI 10.18522/1995-0640-2020-1-62-71